Analysis of Small Traders’ Business Development in Dili City as An Effort To Increase Income (International Journal of Scientific Research and Management (IJSRM), 2025)
Small Traders are business actors who conduct trade in goods and/or services using movable and immovable business facilities, using infrastructure in the city of Dili, social facilities, public facilities, land and buildings owned by the government and/or private sector which are temporary or non-permanent. Dili City is the capital city of Timor Leste which in addition to being the capital city of the country is also the largest city in RDTL in terms of economic activity, population, government and so on. The problems faced by small traders in the city of Dili are the first marketing problem caused by the lack of buyers coming because many people in the city of Dili do not know the location of the traders, causing the location of the traders to be quiet and having an impact on their income levels. Second, the problem of working hours is caused by the lack of long working hours causing the income level to be less than optimal. Third, the price problem is caused by a lack of interaction between fellow traders so that the prices set are different from other traders, causing consumers to prefer relatively cheaper prices so that the income level of traders is less than optimal. Data collected through primary data, primary data obtained from the results of direct observation and interviews with consumers as respondents. The data analysis technique taken by the author is descriptive analysis and inferential analysis using the Structural Equation Model or SEM with the alternative Path Partial Least Square or Path PLS. From the results of the hypothesis test, it can be concluded that the location of selling on income has a positive and significant effect on income. If the location is closer to public facilities and environmental security and comfort, the income will be even better. The length of selling on income has a positive and significant effect on income. If the length of selling is getting better, it can optimize income. Price on income has a positive and significant effect on income. If the price set is appropriate, the income will be even better.